Do visitors attract or repel vertebrates in an urban park in the Brazilian Atlantic Forest? - Zaú, André Scarambone; Freitas, Gustavo Pena; Oda, Gabriela Akemi Macedo (Revista Brasileira de Ecoturismo (RBEcotur), 2015)
Ecotourism is an important tool for biodiversity conservation in protected areas. However, high visitation rates and intensive public use can affect the wildlife. The present study aimed to evaluate vertebrate foraging in areas under different levels of human influence in the Tijuca National Park, a protected area within the metropolitan area of Rio de Janeiro, Brazil. We used baits to attract vertebrates in areas with and without visitor facilities, at distances of 5, 35, and 100 meters from the road. We have analyzed the removal of bait by vertebrates in such treatments and identify higher consumption associated to greater human presence. The presence of visitors and visitor facilities (e.g., parking lots, barbecue pits, picnic tables, and playgrounds) significantly increases bait consumption. Park managers should consider the negative impacts of tourism on wildlife searching for ways to minimize them. RESUMO O ecoturismo é uma importante ferramenta para a conservação da biodiversidade em áreas protegidas. No entanto, as altas taxas de visitação e uso público intensivo podem afetar a fauna em áreas protegidas. O objetivo deste estudo foi avaliar o forrageamento de vertebrados em áreas sob diferentes influências antrópicas no Parque Nacional da Tijuca: uma unidade de proteção integral dentro da metrópole do Rio de Janeiro, Brasil. Foram usadas iscas em áreas com e sem infraestrutura para visitantes, em distâncias de 5, 35 e 100 metros das margens da estrada, dentro de cada sítio de estudo. Análises apontaram que em áreas onde a presença humana é menos constante, o consumo de iscas de bananas foi menos intenso. A interferência causada por visitantes do parque sobre a intensidade do consumo de isca é significativa e influenciada por estruturas de visitação como estacionamento, churrasqueiras, mesas de piquenique e playground. Gestores de parques devem considerar tais impactos do turismo, visando minimizar influências negativas sobre a fauna. PALAVRAS-CHAVE: Gestão de Unidade de Conservação; Uso Público; Parque Nacional da Tijuca; Ecoturismo; Efeito de Borda.